The Coffee Protective Effect on Catalase System in the Preneoplastic Induced Rat Liver - Cristiana Schmidt de Magalhães; Jéssica Emi Takarada; Nathália Costa Carvalho; Dayene do C. Carvalho; Felipe Lopes de Andrade; Eric Batista Ferreira; Pedro Orival Luccas; Luciana Azevedo (Journal of Chemistry)
This study aimed to evaluate the effect of organic/conventional coffee in liver tissues in the cancer process, taking into account the level and activities of catalase. The experiments were carried out with 8 groups of rats during 12 weeks. They received two injections of ethylenediaminetetraacetic acid solution 1.5% (v/v) prepared in 0.9% NaCl or 1,2-dimethylhydrazine (DMH) subcutaneous dose of 40 mg·kg−1·bw−1 for 2 weeks. The organic/conventional coffee infusions were at 5, 10, and 20% and were incorporated to feed (100 mL of infusion·kg−1 of diet). The catalase activity showed a decrease for livers which received DMH and DMH plus organic coffee at 5% and 10%. However, an increase was observed for those receiving organic 20% and conventional 10% coffee, slowing down and favoring the reversibility of the carcinogenic process. By SDS-PAGE, we observed an intensity decrease of 59 kDa bands, as the percentage of coffee was increased. The iron concentration (by ET-AAS) confirmed the electrophoretic results, suggesting that the DMH influenced the catalase expression conditions, reducing the activity by the loss of iron ions. Thus, the coffee may restore the catalase system in the liver, exerting its chemopreventive effects.